PENGARUH SERVICE PERFORMANCE, CUSTOMER EXPERIENCE, DAN VISIBILITY FOODSTAGRAM TERHADAP REPURCHASE INTENTION KONSUMEN STARBUCKS COFFEE - Luh Karenina Savitri Masna; Christina Whidya Utami; Endi Sarwoko (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the effect of service performance, customer experience, and visibility foodstagram on the repurchase intention of Starbucks Coffee consumers. This research was motivated by the strong position of Starbucks Coffee in the Indonesian coffee shop market, while several consumer responses indicate challenges related to service quality, customer experience, and digital visibility. This study used a quantitative approach with an associative causal research design. The sample consisted of 80 Starbucks Coffee consumers who had made at least one purchase. The sampling technique used was convenience sampling. Data were collected using questionnaires distributed directly and online through Google Forms. The data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination with SPSS. The results showed that service performance, customer experience, and visibility foodstagram had a positive and significant effect on repurchase intention. Service performance was the most dominant variable influencing repurchase intention. The coefficient of determination showed that the three independent variables explained 62.2% of the variation in repurchase intention, while the remaining 37.8% was explained by other factors outside the research model. These findings indicate that improving service quality, strengthening customer experience, and optimizing foodstagram visibility are important strategies to encourage consumer repurchase intention.